Food science kitchen mysteries revealed - Learning seed (Illinois : Learning Seed, 2000)
This program shows why we whip cream and beat eggs. Why onions cause tears and what causes bread to rise, popcorn pop, and gelatin gel. Simple language explains complex scientific phenomena
Why eggs crack when boiled -- Why corn pops -- Why cream whips --why we beat eggs -- Why bread rises -- Why pastry puffs -- Why bread is short and quick -- Why soda pops -- Why some peppers are hot -- Why garlic works
Title from title screen
DVD Format
Keywords: Cookery; Food; Gastronomy